Keragaman sekuen DNA fragmen gen penyandi ACCase subunit BCCP dari tiga tipe kelapa sawit Variability of DNA sequence of gene fragment encoding BCCP subunit of ACCase from three types of oil palm - Asmini BUDIANI; Djoko SANTOSO; A.R. PURBA PURBA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2007)
SummaryHeteromeric acetyl-CoA carboxylase (ht-ACCase) is one of key enzymes in palm oilbiosynthesis. Isolation and characterization ofthe gene is an important step in metabolicengineering to increase palm oil content andquality. The objective of this research was toisolate DNA fragment of gene encoding biotincarboxyl carrier protein (BCCP) subunit of ht-ACCase from three different oil palm types(Simalungun, Hibrida and Backcross) andinvestigate the variation of its DNA sequence.Total RNA was isolated from the mesocarp ofoil palm. DNA fragment encoding BCCP wasamplified by means of Reverse TranscriptasePolymerase Chain Reaction (RT-PCR) usingspecific primers with total RNA as a template.The products of RT-PCR were then purifiedfrom the gel, cloned and sequenced. The DNAsequences were analyzed for their homologiesto BCCP gene using BlastN and aligned todetect the sequence variability using ClustalWprogram from BioEdit. The results show thatone of the two RT-PCR products at about 300bp was highly homologous with the geneencoding BCCP from Glycine max, Brassicanapus and Arabidopsis thaliana. Nucleotidesequences of that BCCP fragments from thethree types of oil palm displayed some degreesof variability. Further investigation is neededto analyze the variability of the DNA sequencesof the full-length gene in relation with oilcontent or other characterRingkasanAsetil-CoA karboksilase heteromerik (ht-ACCase) merupakan salah satu enzim kuncidalam biosintesis minyak sawit. Isolasi dankarakterisasi gen tersebut merupakan langkahpenting dalam upaya rekayasa metabolismeuntuk peningkatan rendemen dan kualitasminyak sawit. Penelitian ini bertujuan untukmengisolasi fragmen DNA penyandi subunitbiotin carboxyl carrier protein (BCCP) dari ht-ACCase dari tiga tipe kelapa sawit yang ber-beda (Simalungun, Hibrida dan Backcross)dan mempelajari keragaman susunan nukleo-tidanya. RNA total diisolasi dari mesokarpbuah sawit. Fragmen gen penyandi BCCPdiamplifikasi dengan Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) meng-gunakan primer spesifik dan templat RNA total.Fragmen hasil RT-PCR dimurnikan dari gel,diklon kemudian disekuen. Sekuen DNA yangdiperoleh dianalisis homologinya dengan genBCCP menggunakan BlastN dan disejajarkanuntuk mengetahui keragamannya mengguna-kan program ClustalW dari BioEdit. Hasilnyamenunjukkan bahwa satu dari dua fragmenhasil RT-PCR yang berukuran sekitar 300 pbmemiliki homologi yang tinggi denganfragmen gen penyandi BCCP dari Glycine max,Brassica napus dan Arabidopsis thaliana.Urutan nukleotida fragmen BCCP dari ketigatipe kelapa sawit menunjukkan keragaman.Perlu analisis lebih lanjut mengenai keragamansekuen DNA dari gen lengkapnya dan dikajihubungannya dengan akumulasi minyak ataukarakter lain